Nuisance alga reduces lake partial pressure of carbon dioxide and carbon flux to the atmosphere in boreal lakes - Münzner, Karla ; 0000-0002-7568-8095; Lindström, Eva S.; Rohrlack, Thomas (Limnology and Oceanography, 2025)
Boreal lakes are generally seen as sources of carbon dioxide (CO2) to the atmosphere, even though a part of them are periodically undersaturated with CO2 and have the potential to be net-autotrophic. This undersaturation is the result of photosynthetic activity by phytoplankton, especially flagellated species like Gonyostomum semen, which form high-biomass blooms in brown water lakes. We hypothesized that CO2 reduction by G. semen is common across boreal lakes, and that those reductions vary with dissolved organic carbon (DOC) concentrations across lakes. In our field study, we explored how G. semen abundance affected the partial pressure of CO2 (pCO2) in the water column and the estimated carbon flux to the atmosphere in four lakes in Sweden and Norway in summer 2021. We found that lake pCO2 and carbon flux to the atmosphere decreased with increasing G. semen abundances, though all lakes still emitted CO2 to the atmosphere. High DOC concentrations acted as a limiting factor for G. semen growth, indicating that G. semen's potential to reduce pCO2 and carbon flux to the atmosphere weakens with increasing DOC concentrations. Still, G. semen's impact on pCO2 and carbon flux to the atmosphere is relevant in a wider spatial context, because G. semen and other motile flagellated species are expected to increase in range and bloom frequency in boreal lakes. Thus, we propose that CO2 fixation via photosynthesis is an underestimated factor in controlling CO2 dynamics in boreal lakes, and that it should be included in large-scale CO2 budget calculations.
Publisher Copyright: © 2025 The Author(s). Limnology and Oceanography published by Wiley Periodicals LLC on behalf of Association for the Sciences of Limnology and Oceanography.